Dietary habits associated with growth development of children aged < 5 years in the Nouna Health and Demographic Surveillance System, Burkina Faso - Mank, Isabel; Vandormael, Alain; Traoré, Issouf; Ouédraogo, Windpanga Aristide; Sauerborn, Rainer; Danquah, Ina (Nutrition journal, 2020)
Knowing which dietary habits are associated with child growth could lead to better long-term health outcomes and improve the design of food-based interventions. We aimed to identify dietary habits that are associated with the growth development of children aged < 5 years living in rural Burkina Faso.